Television and radio repairing - Markus, John. ([S.l.] : McGraw-Hill Inc.,US, 1961)
'A practical manual of television and radio servicing containing simple step-by-step instructions for testing, repairing, and replacing all parts. 1961 2nd Edition from McGraw-Hill.